Lean Six Sigma implementation case studies. (27th December 2005) - Pickrell, Gary; Lyons, Harry J.; Shaver, Judy
In this paper, we review the rational and potential framework for combining principles of Six Sigma with those of Lean Manufacturing and present two case studies for Lean Six Sigma Projects completed at a worldwide manufacturer of precision slip ring and integrated motion systems for high performance requirements in military and commercial aircraft, satellites and space vehicles, missiles, and automated industrial machinery. Lean Manufacturing and Six Sigma business improvement programmes are often implemented separately. A growing number of companies have realised these programmes are a dynamic, synergistic force rather than two separate and competing initiatives. A proprietary military application case study is presented whereby substantial documented improvements in reductions of cost, cycle time, customer returns and inventory, and an increase in production capacity will be presented. In the second study, an automated document control system was implemented, reducing customer rejections and manufacturing delays due to document revision errors during production.